2022
DOI: 10.1177/20499361221103877
|View full text |Cite
|
Sign up to set email alerts
|

Medication for opioid use disorder at hospital discharge is not associated with intravenous antibiotic completion in post-acute care facilities

Abstract: Background: People with opioid use disorder and severe infections may complete their prolonged courses of outpatient parenteral antimicrobial therapy at a post-acute care facility due to adherence and safety concerns. We hypothesized that treatment with medications for opioid use disorder, such as methadone and buprenorphine, would increase antibiotic completion in these facilities. Methods: We performed a retrospective cohort study of people with opioid use disorder and severe infections who were discharged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…O’Kane et al showed no statistical difference in all-cause 180-day readmission or mortality when prescribing buprenorphine at discharge [ 12 ]. Traver et al showed no association with the completion of outpatient parenteral antimicrobial therapy [ 20 ]. In this study, the authors acknowledged the possible selection bias in the use of ICD codes in potentially missing patients with incomplete documentation as well as the inclusion of patients who use prescription opioids and do not have a substance use disorder.…”
mentioning
confidence: 99%
“…O’Kane et al showed no statistical difference in all-cause 180-day readmission or mortality when prescribing buprenorphine at discharge [ 12 ]. Traver et al showed no association with the completion of outpatient parenteral antimicrobial therapy [ 20 ]. In this study, the authors acknowledged the possible selection bias in the use of ICD codes in potentially missing patients with incomplete documentation as well as the inclusion of patients who use prescription opioids and do not have a substance use disorder.…”
mentioning
confidence: 99%